Peranan Bimbingan Teknis Penguatan Akreditasi Bagi Pendidik dan Tenaga Kependidikan PAUD Aisyiyah Se Kota Kendari - Halima; Asrul; Nurlina (LEMBAGA PENELITIAN & PENGABDIAN MASYARAKAT UNIVERSITAS SINGAPERBANGSA KARAWANG, 2023)
This study aims to analyze the role of technical guidance in strengthening accreditation for educators and education personnel. Through a qualitative approach, this study explores understanding, impacts, barriers, and improvement recommendations related to the accreditation process in educational institutions. The results showed that most educators and education personnel have an adequate understanding of the concept of accreditation, but challenges arise in its practical implementation. Technical guidance was found to have a positive impact in increasing the understanding and readiness of educators and education personnel to face the accreditation process. While effective, variations in impact point to the need for a more personalized approach. The impact of strengthening accreditation includes improving the quality of education, the reputation of institutions, and the motivation of educators This study aims to analyze the role of technical guidance in strengthening accreditation for educatorsand education staff. However, some barriers such as requirements complexity, resource limitations, and resistance to change were identified. Recommendations for improvement involve developing clearer guidelines, additional training, and utilization of technology. In conclusion, this study highlights the importance of continuous efforts to support effective implementation of accreditation, overcome barriers, and ensure the central role of educators and education personnel in achieving high standards of education quality